Surveillance for presumed BD-IPMN of the pancreas: stability, size, and age identify targets for discontinuation - Marchegiani, Giovanni; Pollini, Tommaso; Burelli, Anna; Han, Youngmin; Jung, Hye-Sol; Kwon, Wooil; Rocha Castellanos, Dario Missael; Crippa, Stefano; Belfiori, Giulio; Arcidiacono, Paolo Giorgio; Capurso, Gabriele; Apadula, Laura; et al. (Gastroenterology, 2023)
Background & Aims - Currently, most patients with branch duct intraductal papillary mucinous neoplasms (BD-IPMN) are offered indefinite surveillance, resulting in health care costs with questionable benefits regarding cancer prevention. This study sought to identify patients in whom the risk of cancer is equivalent to an age-matched population, thereby justifying discontinuation of surveillance. - Methods - International multicenter study involving presumed BD-IPMN without worrisome features (WFs) or high-risk stigmata (HRS) at diagnosis who underwent surveillance. Clusters of individuals at risk for cancer development were defined according to cyst size and stability for at least 5 years, and age-matched controls were used for comparison using standardized incidence ratios (SIRs) for pancreatic cancer. - Results - Of 3844 patients with presumed BD-IPMN, 775 (20.2%) developed WFs and 68 (1.8%) HRS after a median surveillance of 53 (interquartile range 53) months. Some 164 patients (4.3%) underwent surgery. Of the overall cohort, 1617 patients (42%) remained stable without developing WFs or HRS for at least 5 years. In patients 75 years or older, the SIR was 1.12 (95% CI, 0.23-3.39), and in patients 65 years or older with stable lesions smaller than 15 mm in diameter after 5 years, the SIR was 0.95 (95% CI, 0.11-3.42). The all-cause mortality for patients who did not develop WFs or HRS for at least 5 years was 4.9% (n = 79), and the disease-specific mortality was 0.3% (n = 5). - Conclusions - The risk of developing pancreatic malignancy in presumed BD-IPMN without WFs or HRS after 5 years of surveillance is comparable to that of the general population depending on cyst size and patient age. Surveillance discontinuation could be justified after 5 years of stability in patients older than 75 years with cysts <30 mm, and in patients 65 years or older who have cysts ≤15 mm.
Available online 4 July 2023, Version of Record 21 September 2023
Gesehen am 14.01.2025